Student Needs in Differentiated Learning Using Digital Media Materials Based on the Renderforest 3d Explainer Toolkit - Hardiansyah, Framz; Afifah, Yulia Dwi; Febria, Bella Helliana; Prasetyo, Adit Ayyubi; Alif, Farhan (Journal of Practice Learning and Educational Development, 2026)
This study discusses differentiated learning that allows educators to identify, investigate, and meet the diverse learning needs of each student by adjusting the approach based on the needs, readiness, interests, and learning profiles of students. This study uses the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method known as Systematic Literature Review. The results of the study indicate that differentiated learning is a teaching method where teachers use various teaching techniques to meet the individual needs of each student, such as existing knowledge, learning styles, interests, and understanding of the subject matter. In this context, the Renderforest application is a solution as a digital platform designed to create interesting animations and learning videos, with a 3D explainer toolkit template that allows teachers to create materials according to student needs through attractive visual features that are suitable for students with diverse learning styles. In conclusion, differentiated learning by utilizing digital-based learning media such as Renderforest can be an effective solution in meeting the diverse learning needs of students, increasing motivation, and creating a more interesting and relevant learning experience.